An International Investigation of Intimate Partner Violence-Related Training Among Mental Health Professionals - Burns, Samantha (Université d'Ottawa / University of Ottawa, 2021)
Intimate partner violence (IPV), including physical, psychological, and sexual violence towards a partner, is a human rights violation that is associated with the development of a multitude of short- and long-term physical and mental health problems (WHO, 2013). IPV survivors are at greater risk of developing mood, anxiety, and trauma- and stressor-related disorders (García-Moreno et al., 2005). Public health guidelines recommend screening for IPV in mental health settings (WHO, 2013). However, most mental health practitioners do not routinely assess for IPV in their practice (Howard et al., 2010). Lack of training in how to assess for and respond to IPV has been identified as an important barrier for IPV assessment in mental health settings (Trevillion et al., 2016). IPV-related training has been linked to positive outcomes for clinicians, including higher ratings of perceived knowledge and confidence in addressing IPV (Forsdike et al., 2019). Yet, studies suggest that approximately one quarter to one half of mental health professionals have never received IPV-related training (Murray et al., 2016; Nyame et al., 2013). To address this gap, the WHO advanced a series of evidence-based training recommendations (WHO, 2013). At present, there is a dearth of research exploring the degree to which global mental health providers’ experiences of training resemble WHO guidelines. Furthermore, few studies have investigated factors that contribute to clinicians’ likelihood of participating in IPV-related training, and reasons for obtaining training are not well understood. There has also been no previous research into the relationship between mental health professionals’ experiences of training and their accuracy in correctly identifying IPV. The present thesis, consisting of two studies, sought to assess global mental health providers’ IPV-related training experiences, including factors that influence the probability of participating in training and the relationship between training and diagnostic accuracy. In study 1, mental health professionals’ IPV-related training experiences were surveyed, and factors that may contribute to the likelihood of participating in training were explored (e.g., IPV prevalence, norms, and legislation, and professional experience with IPV). The relationship between IPV-related training and knowledge and experience of relationship problems was also examined; 321 specialized mental health professionals (psychologists and psychiatrists) from 24 countries participated in an online survey. Participants responded to a series of questions regarding the content, duration, and frequency of their IPV-related training based on WHO recommendations, and rated their level of knowledge and experience with relationship problems. Descriptive analyses showed that nearly half of participants (46.9%) had never received IPV-related training. Approximately half of those who received training (49.4%) indicated that their training followed WHO recommendations. Logistic regressions revealed that participants who were from countries with relatively better implemented laws addressing IPV and participants who encountered IPV more often in clinical practice were more likely to have received training. Furthermore, participants who received training were more likely than those without training to report higher knowledge and experience of relationship problems. Findings highlight global challenges with regards to IPV-related training. They suggest that clinicians’ likelihood of participating in training is related to their clinical contact with IPV and the institutional context in which they practice. Study 2 investigated the relationship between IPV-related training and clinicians’ diagnostic accuracy in the context of relationship problems, using the same sample as study 1. Chi-square analyses evaluated relationships between IPV-related training and clinicians’ performance while assessing for clinically significant relationship problems (RPM) in case-controlled vignettes across two study conditions: RPM present (i.e., when the task was to correctly identify RPM) and RPM absent (i.e., when the task was to correctly identify that there was no RPM; normative relationship problems were presented). Results showed that participants who received IPV-related training were more likely to perform better than those without training in the RPM present condition, but not in the RPM absent condition. In the RPM present condition, participants were more likely to respond correctly when their training was more recent and more closely resembled WHO recommendations for training. In the RPM absent condition, a similar percentage of participants with training (60-78%) and without training (45-76%) misclassified normative relationship problems as clinically significant RPM. Overall, findings suggest that IPV-related training is related to improved diagnostic accuracy in the context of relationship problems. WHO recommendations for training are supported.
Keywords: Intimate partner violence; Training; Mental health professionals; Cross-national